Robert K. Merton sociology of science and sociology as science - Calhoun, Craig J., 1952- (Columbia/SSRC book., 2010)
"Robert K. Merton (1910-2003) was one of the most influential sociologists of the twentieth century, producing clear theories and innovative research that continue to shape multiple disciplines. Merton's reach can be felt in the study of social structure, social psychology, deviance, professions, organizations, culture, and science. Yet for all his fame, Merton is only partially understood. He is treated by scholars as a functional analyst, when in truth his contributions transcend paradigm.